(untitled) (Annals of Medical Research, 2023)
Aim: The aim of our study is to determine the method with the least recurrence and complication rate in laparoscopic hernia surgery. For this reason, the purpose of cutting the graft is to give it a closer and appropriate shape to the anatomy and thus to minimize the recurrence rate. Materials and Methods: A total of 142 patients with hernias, 135 men and 7 women, were included in the study. The cases were divided into two groups; the conventional shape of the graft was applied to the first group without slit, in the second group; the graft was cut in the middle to spread around the pampiniform plexus, and the hernia sac and pampiniform plexus were dissected, and then spread around the pampiniform plexus with slit. The methods of spreading around the inguinal cord by cutting versus spreading on the inguinal cord without cutting were compared. Results: While the slit mesh status of those with postoperative testicular edema was 100% present and 0% absent, and a statistically significant difference was determined between the groups (p=0.027). The patients’ time to return home after surgery was statistically significantly higher in the slit mesh present group compared to the absent group (p=0.001). A statistically significant difference was found when those who did not have reoperation and those who had reoperation status were compared (p=0.044). Conclusion: It was concluded that this new approach minimizes early and late recurrences with faster recovery after repair of laparoscopic extraperitoneal inguinal hernia. We suggest a slit mesh method by changing the shape and spreading the mesh without using any fixation material can also be used as a fixation method such as self-adhesive mesh and fibrin glue.